Fast and reliable mini-prep RNA extraction from Neurospora crassa - V. SOKOLOVSKY; R. KALDENHOFF; M. RICCI; V. E. A. RUSSO (Fungal Genetics Reports, 1990)
We have developed a method for isolating high quality total RNA from N. crassa mycelia that reliably yields large quantities. It is possible to extract more than 50 minipreps at once.